AGENCY CONFLICT OF FREE CASH FLOW ON EXECUTIVE COMPENSATION AND THE ROLE OF INSTITUTIONAL OWNERSHIP - Amanah, Lailatul; Setyawardani, Lydia; Dewi, Mega Arisia (International Conference of Business and Social Sciences, 2022)
The study was to examine the effect of free cash flow and company performance on executive compensation with institutional ownership as a moderating variable. Executive compensation is an issue of fierce debate, making it a continuously interesting object to study. The sample was manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period selected using the purposive sampling technique. A sample of 147 companies was selected for 5-year period of data collection, resulting in 509 pooled data. The free cash flow variable was measured using the Ross’ (2013) measure, executive compensation was measured by overall compensation received by managers, company performance was measured by return on investment (ROA), and institutional ownership was measured by the institutions’ shareholding. Data were analyzed using multiple linear regression modified with moderating variables. Results showed that free cash flow and company performance had a positive effect on executive compensation. Institutional ownership was capable of moderating the positive effect of company performance on executive compensation, while the effect of free cash flow on executive compensation was not significant. References Ankono, Henri. 2016. Free Cash Flow and Eecutive Compensation. International Journal of Business and Social Science. Vol 7. No. 4 April. Bernandhi. R. 2013. Pengaruh Kepemilikan Manajerial, KepemilikanInstitusional, Kebijakan Deviden, Leverage, Ukuran Perusahaan Terhadap Nilai Perusahaan. Universitas Diponegoro. Semarang. Brigham, E. F., & Houston, J. F. 2009. Fundamentals of financial management, concise Edition. Cengage Learning. Daeng. D. A. 2017. Tantiem atau Bonus Bagi Korporasi BUMN. Eduardus, T., Husnan, S., & Hanafi, M. M. 2012. Determinants of bank profit efficiency: Evidence from Indonesia. International Journal of Economics and Finance Studies, 4(2), 163-173. Gitman, Lawrence J., and Chad J. Zutter Ghozali, I. Dan Fuad. 2015. Teori Akuntansi. Edisi 4. Universitas Diponegoro. Semarang. Harahap, S. S.. 2011. Analisis Kritis Atas Laporan Keuangan. Raja Grafindo Persada, Jakarta. Hendro dan R. Wardhani. 2015. Pengaruh Agency Cost of Free Cash Flow Terhadap Tingkat Konservatisme dan Pengujian Efek Moderasi Kebijakan Hutang, Pendistribusian Kas, Persistensi Kas, dan Tata Kelola Perusahaan. Jurnal Akuntansi dan Keuangan. Vol 17. No.1. Mei 2015. Honggowati, S., Rahmawati, R., Aryani, Y. A., & Probohudono, A. N. 2017. Corporate governance and strategic management accounting disclosure. Indonesian Journal of Sustainability Accounting and Management, 1(1), 23-30. Jensen, M. C., & Meckling, W. H. 1976. Theory of the firm: Managerial behavior, agency costs and ownership structure. Journal of financial economics, 3(4), 305-360. Kargar, E. F., & Ahmadi, G. R. 2013. The relationship between free cash flows and agency costs levels: Evidence from Tehran stock exchange. Research Journal of Finance and Accounting, 4(14), 51-65. Kieso, D.E., J.J. Weygant, dan T.D. Warfield. 2011. Intermediate Accounting. Vol. 1 IFRS Edition. John Wiley and Sons. USA. Kussulisty, M. J. W. A., & Mahfudz, M. 2016. Analisis Faktor-Faktor Yang Memengaruhi Keputusan Hedging Dengan Derivatif Valuta Asing (Studi Pada Perusahaan Non-Finansial Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2011–2014). Diponegoro Journal of Management, 5(3), 13-26. Lako. A. 2007. Kelayakan Sistem Kompensasi Manajemen Untuk Eksekutif. Universitas Katolik Soegijapranata, Semarang. La Porta, R., Lopez-de-Silanes, F., Shleifer, A., & Vishny, R. 2000. Investor protection and corporate governance. Journal of financial economics, 58(1-2), 3-27. Lindianasari. 2013. Corporate Growth and CEO Compensation: Case from Indonesia. Indonesian Journal and Accounting Risearch. P 25-37. Luthfiah, A. A., & Suherman, S. 2018. The effects of financial performance toward firm value with ownership structure as moderating variable (the study on manufacturing companies listed in Indonesia Stock Exchange in the period of 2012-2016). Journal of Business and Behavioural Entrepreneurship, 2(1), 18-27. Maharani, W. P., and Utami, E. R. 2019. The Influence Of Institutional Ownership Towards Executive Compensation Considered By The Performance Of The Company. Jurnal Reviu Akuntansi dan Keuangan, 9(1), 85-96. Murphy, K. J., & Oyer, P. 2001. Discretion in executive incentive contracts: Theory and evidence. Available at SSRN 294829. Putri, C. D. 2013. Pengaruh Corporate Governance Dan Karakteristik Perusahaan Terhadap Pengungkapan Tanggung Jawab Sosial Perusahaan Di Dalam Sustainability Report (Studi Empiris Perusahaan yang Terdaftar di BEI). Jurnal Akuntansi, 1(3). Ross, Stephen A., Westerfield, Randolph W., and Jaffe, Jeffrey. 2013. Corporate Finance. 10th Edition. New York: McGraw-Hill. Saleh, A., & Sudiyatno, B. 2013. Pengaruh rasio keuangan untuk memprediksi probabilitas kebangkrutan pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia. Dinamika Akuntansi Keuangan dan Perbankan, 2(1). Sari, D. A., & Riduwan, A. 2015. Kinerja Keuangan, Corporate Social Responsibility, Good Corporate Governance dan Nilai Perusahaan. Jurnal Ilmu dan Riset Akuntansi (JIRA), 4(5). Sugiyono. 2012. Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung: Alfabeta. Suherman, S., Pardede, Y. Y., & Mardiyati, U. 2016. Pengaruh kinerja perusahaan, corporate governance, dan karakteristik eksekutif terhadap kompensasi eksekutif. Jurnal Keuangan dan Perbankan, 20(1), 1-9. Suryatiningsih, N., & Siregar, S. V. 2009. Pengaruh skema bonus direksi terhadap aktivitas manajemen laba: Studi empiris pada BUMN periode tahun 2003-2006. Jurnal Simposium Nasional Akuntansi, 11. Trisna, I. K. E. R., & Gayatri, G. 2019. Ukuran Perusahaan Memoderasi Pengaruh Free Cash Flow dan Leverage Terhadap Kebijakan Dividen. E-Jurnal Akuntansi, 26(1), 484. Usman,M. 2015. Role of Board and Firm Performance in Determination of CEO Compensation: Evidence from Islamic Republic of Pakistan. Pakistan journal of Commerce and Social Science. 9(2).P641-657. Widarti, S., & Pramajaya, J. 2018. The Effect Of Profit Management On Company Performance. International Journal of academic research in Economics and Management sciences, 7(4), 44-63. Widyati, M. F. 2013. Pengaruh dewan direksi, komisaris independen, komite audit, kepemilikan manajerial dan kepemilikan institusional terhadap kinerja keuangan. Jurnal ilmu manajemen, 1(1), 234-249.